Rare presentation of hematometrocolpos with didelphys uterus in a teenager - P. Vedak; D.B. Bhusare; P. Patil (Elsevier, 2021)
Hematometrocolpos is one of the rare Mullerian anomaly presenting as abdominal pain during the age of menarche. We present a case of 14 year old girl presenting with amenorrhea to our hospital with imperforate hymen who on examination and investigation was diagnosed as a case of hematometrocolpos. It is a must know Mullerian anomaly to the surgeons as diagnosis is a challenge and need high suspicion for surgical intervention and to prevent future rise in rate of infertility.